2022
DOI: 10.1371/journal.pone.0262668
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the tingle: Investigating the association between the Autonomous Sensory Meridian Response (ASMR), neuroticism, and trait & state anxiety

Abstract: The Autonomous Sensory Meridian Response (ASMR) is an intensely pleasant tingling sensation originating in the scalp and neck and is elicited by a range of online video-induced triggers. Many individuals now regularly watch ASMR videos to relax, and alleviate symptoms of stress and insomnia, all which are indicative of elevated levels of anxiety. Emerging literature suggests that ASMR-capable individuals are characterised by high trait neuroticism, which is associated with a tendency to experience negative emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…ASMR has been suggested to promote positive emotion, such as calmness and excitement and even beyond self-reported feelings of physiological measures, to reduce heart rate and increase skin conductance level in ASMR responders while watching ASMR videos [10]. Previous study also indicates that watching ASMR video can alleviate anxiety state in the participants who experienced ASMR [42]. These studies imply that there is an association between ASMR and emotion.…”
Section: Discussionmentioning
confidence: 93%
“…ASMR has been suggested to promote positive emotion, such as calmness and excitement and even beyond self-reported feelings of physiological measures, to reduce heart rate and increase skin conductance level in ASMR responders while watching ASMR videos [10]. Previous study also indicates that watching ASMR video can alleviate anxiety state in the participants who experienced ASMR [42]. These studies imply that there is an association between ASMR and emotion.…”
Section: Discussionmentioning
confidence: 93%
“…Despite this great popularity and the possible therapeutic potential of ASMR, a scientific evaluation of ASMR has hardly been conducted so far. First effects were recently demonstrated on aspects associated with mental health (inducing pleasant affect [ 1 3 ]; improving sleep quality [ 4 ]; inducing relaxation [ 3 , 5 ]; alleviating state anxiety [ 6 ]). Furthermore, initial evidence suggests that ASMR experience also triggers physiological responses.…”
Section: Introductionmentioning
confidence: 99%
“…Different ASMR-responder rates have been provided in two studies: While Roberts et al [ 15 ] state that 28 percent regard themselves as ASMR-responders, Swart et al [ 16 ] report that 38 percent consider themselves to be responding to ASMR. Initial evidence suggests that ASMR experience is associated with specific personality characteristics, such as neuroticism [ 6 , 17 ] or openness to experience [ 10 , 17 ], the latter including greater openness towards aesthetic experiences and positive stimuli [ 18 ]. Furthermore, a link with mental health related traits such as mindfulness has been reported [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While research showed that for battling sensations of being lonely and random dark moods individuals are increasingly employing autonomous sensory meridian response (ASMR) stuff to relax and alleviate anxiety and depression. A recent study demonstrates that ASMR-capable persons have high trait neuroticism, which is associated with unpleasant feelings like anxiety (Eid et al, 2022 ). Relatively little attention has been paid to individuals with anxiety disorder specifically those who possessed dark characteristics suffering from social loneliness due to deadly COVID 19.…”
Section: Introductionmentioning
confidence: 99%
“…It is now feasible to characterize ASMR experiences, which are psychologically relaxing triggers that repeat and control anxiety, despair, boredom, and other core emotions (Baker, 2018 ). ASMR videos include dancing competitions, haircuts, massage tutorials, and customer service role plays, that can ultimately alleviate sorrow, depression, and anxiety (Baker, 2018 ; Eid et al, 2022 ). Moreover, Gomes Arrulo et al ( 2021 ) looked at the impact of music listening and dark personality characteristics on stress perception and cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%